Functional imaging and modeling of the heart : 10th International Conference, FIMH 2019, Bordeaux, France, June 6-8, 2019, Proceedings /: 10th International Conference, FIMH 2019, Bordeaux, France, June 6-8, 2019, Proceedings. ([2019]) - Unknown
No abstract available